Reliability of LoSCAT score for activity and tissue damage assessment in a large cohort of patients with Juvenile Localized Scleroderma - Anna Agazzi; Gloria Fadanelli; Fabio Vittadello; Francesco Zulian; Giorgia Martini (BMC, 2018)
Abstract Objectives To assess reliability of the two indexes of Localized Scleroderma Cutaneous Assessment Tool (LoSCAT), the modified Localized Scleroderma Skin Severity Index (mLoSSI) and the Localized Scleroderma Skin Damage Index (LoSDI), when applied by clinicians with different experience in scoring and managing patients with JLS. Secondary aim was to compare LoSCAT and infrared thermography (IRT) in monitoring lesions over time. Methods Consecutive children with Juvenile Localized Scleroderma (JLS) were blindly evaluated by three examiners with different experience in Paediatric Rheumatology and with no experience in LoSCAT use. At each visit, patients were assessed by LoSCAT and IRT. Sensitivity to change of LoSCAT and IRT was assessed in a group of patients 3-6 months later. Inter-rater reliability was assessed by Intraclass Correlation Coefficient (ICC) and variance analysis (ANOVA). Findings Forty-seven patients (129 lesions) entered the study, and 26 (79 lesions) were re-evaluated with same modality after 4.5 (SD 1.5) months. mLoSSI showed excellent inter-rater reliability expressed by ICC 0.965 confirmed by ANOVA. Similarly, inter-rater reliability for LoSDI was good (ICC = 0.774) but worse concordance among examiners was observed. A comparable improvement of mLoSSI in all anatomic sites was noted by all examiners in 79 lesions examined in two subsequent visits and was consistent with thermography. Conclusions Different clinical experience in JLS did not influence clinical judgement in mLoSSI which showed excellent concordance, whereas LoSDI is less precise in damage assessment and not completely reliable in monitoring skin changes. Infrared thermography confirms to be a helpful tool for detecting disease activity and reliable in monitoring lesions over time.